Adjustmento of biomedical investigation in Chile - Sotomayor Saavedra, María Angélica (Acta Bioethica, 2008)
This paper analyses the developmento of the normative on human beings' development in Chile since 1990 onwards considering the context of the human rights' treaties. Scientific investigation is analysed from the investigatior's point of view and that of people serving as subjects. It focalizes its attentions on the one that employs pharmaceutical products that are not commercially autorized in the country. It also examines the normatives' evolution regarding the investigation's protections towards its subjects, and the attributions to develop these essays inside the health-care institutions. The work ends with a critical analysis of today's guidelines and with a glance at its challenges.